Implementation of Qatar Debate System in Arabic Language Learning at Naatiq Course Institution Pare Kediri - Anisah, Suria; Huda, Miftahul; Munjiah, Ma'rifatul (Abjadia : International Journal of Education, 2025)
Arabic language learning currently experiences several obstacles, especially in learning speaking skills. However, the course institution ‘Naatiq’ focuses on improving Arabic speaking skills like ‘native speakers’. And the learning method used is debate with the Qatar Debate system. Debate is one of the highest components in speaking skills because it requires good skills in speaking, rhetoric, logical acumen and understanding of the mindset of a theme. This study aims to describe the implementation of the Qatar Debate system in Arabic language learning at Naatiq Pare Kediri course institution. This type of research is descriptive qualitative. Data collection using observation, interviews and documentation. The data analysis technique is based on the theory of Miles and Hurberman which is carried out through three steps namely data reduction, data exposure and data verification or conclusion making. Based on the results of the study, it can be concluded that the application of the Qatar Debate system in Arabic language learning is very suitable for practicing the use of Arabic vocabulary and increasing confidence in speaking Arabic.